(untitled) (Revista Contexto & Educação, 2026)
The objective of this article was to analyze the peculiarities of Food and Nutrition Education (FNE) from the perspective of Health Promotion in the school context. A mapping of scientific productions available on the Capes Journals Portal from 2014 to 2024 was carried out, and the descriptors "Health Promotion" AND "Food and Nutrition Education" AND "School" were used for the search. This is a qualitative research of the bibliographic review type. The corpus analysis was based on the Discursive Textual Analysis (DTA) of Moraes and Galiazzi (2020). The research corpus comprised 10 articles, from which three categories emerged resulting from the comparison of units of meaning: A) Powerful educational interventions related to health, food, and nutrition; B) FNE from the perspective of Health Promotion in the school environment; and C) Integrated Curriculum. The analysis of the categories indicates the need to discuss Health Promotion from a curricular and practical perspective, aiming to remove it from its theoretical pedestal and overcome the idea that it is difficult to conceive of it as a process and lived outcomes. Therefore, the discussion of seeking strategies for implementing Health Promotion actions involving the EAN theme in the school context is heightened.